Structural Analogues of Thyronamines: Some Aspects of the Structure and Bioactivity of 4-[4-(2-Aminoetoxy)benzyl]aniline - Alexander B. Eresko; Elena V. Raksha; Dmitry A. Filimonov; Nadezhda N. Trubnikova; Irina A. Kisilenko; Dorota M. Chudoba (Chemistry Proceedings)
Molecular modelling of the structure and evaluation of the chemical shifts of 1H and 13C nuclei were performed for the 4-[4-(2-aminoethoxy)benzyl]aniline, which is a structural analogue of thyronamines. The intramolecular dynamics of the key structural fragments of 4-[4-(2-aminoethoxy)benzyl]aniline were studied by the PM6-DH2 method as well as at the B3LYP/6-31G(d,p) level of theory. Nonspecific solvation with dimethyl sulfoxide was taken into account within the polarized continuum model. Specific solvation by one and two DMSO molecules was considered within supermolecule approximation. Chemical shifts of the 1H and 13C nuclei were estimated for the most stable conformer of 4-[4-(2-aminoethoxy)benzyl]aniline as well as for its solvates with DMSO. Calculated chemical shifts of the 1H and 13C nuclei are in good agreement with the experimental ones obtained for 4-[4-(2-aminoethoxy)benzyl]aniline in DMSO-d6 solution. Some aspects of the bioactivity of 4-[4-(2-aminoethoxy)benzyl]aniline are discussed.